Nexus between halal certificate, competitive advantage, and entrepreneurial orientation of SMEs in Food and Beverage industry - Nanang Apriliyanto; Nanik Hidayati (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This research aimed to support Small and Medium Enterprises (SMEs) by investigating the correlation between obtaining halal certification, adopting an entrepreneurial orientation, and gaining a competitive advantage in their respective industries.Method — This study is categorized as quantitative research involving a sample size of 105 respondents who are Small and Medium Enterprises (SMEs) owners in the food and beverages sector in Kendal Regency. The primary data used in this research was collected directly by the researchers from the respondents, focusing on aspects such as halal certification, entrepreneurial orientation, and competitive advantage. Structural Equation Modelling (SEM) is employed as the analytical technique in this study.Result — The findings of this research indicate a positive and significant influence of the relationship between halal certification and entrepreneurial orientation on competitive advantage. Additionally, the study reveals a positive and significant impact of halal certification on entrepreneurial orientation. Furthermore, the direct mediating relationship between entrepreneurial orientation and halal certification, as well as competitive advantage, also demonstrates a positive and significant effect.Contribution — This study makes a significant academic contribution by investigating the relationship between halal certification, entrepreneurial orientation, and competitive advantage in the context of Small and Medium Enterprises (SMEs). By filling a knowledge gap in the literature, it enhances our understanding of how these variables are interconnected and their impact on SMEs' competitiveness.